Children's Stereotype Threat in African-American High School Students: An Initial Investigation - J. Thomas Kellow; Brett D. Jones (Arizona State University, 2015)
Stereotype threat refers to the risk associated with confirming a negative stereotype based on group membership. We examined this effect in a sample of African-American high school students. Stereotype threat was manipulated by presenting a visual spatial reasoning test as (a) diagnostic of mathematical ability or (b) a culture and gender fair test of mathematical reasoning. Support was found for the general effect, and while tests of the effect of the manipulation on anxiety and perceptions of ability and expectancies for success were statistically inconclusive, the data trended in the predicted direction. Implications related to the high-stakes testing of African-American students are discussed.